Shifting Breeding Phenology in Eurasian Kestrels Falco tinnunculus: Effects of Weather and Urbanization - Huchler, Katharina; Schulze, Christian H.; Gamauf, Anita; Sumasgutner, Petra (Frontiers in Ecology and Evolution, 2020)
Human-induced climate change and the destruction of natural habitats are two of the main threats to biodiversity worldwide. Animals can use local weather conditions as environmental cues for optimal breeding conditions, but climate change can cause severe phenological mismatches. Migratory species that have a shorter time period for their settlement decision, or species that breed in heavily transformed habitats, might be specifically sensitive to such change. Here, we analyzed the arrival and egg-laying dates of Eurasian kestrels (Falco tinnunculus) in Vienna (415 km2), Austria, gathered by academic and citizen scientists between 2010 and 2018. To identify critical time windows in which weather variables affect phenology, we used a sliding window approach and considered the degree of urbanization as an additional predictor to unravel habitat-dependent relationships. Furthermore, we assessed the relationship between arrival and egg-laying (i.e., the length of the time gap in-between). We found that arrival dates were not influenced by urbanization, and that egg-laying started earlier in drier weather conditions prior to arrival, and earlier in more natural areas than in the urban center. The time gap between arrival and egg-laying was slightly shorter in breeding pairs that arrived later at their nest sites. Our results might indicate a strategy to mitigate later arrival by relatively earlier egg-laying through reducing the length of the courtship period. Such a behavioral adaptation could avoid negative effects of a later onset of breeding on their reproductive success, which is known from previous studies in our urban population.